Satellite Observations of the Tropical Terrestrial Carbon Balance and Interactions With the Water Cycle During the 21st Century. (24th March 2021) - Worden, John; Saatchi, Sassan; Keller, Michael; Bloom, A. Anthony; Liu, Junjie; Parazoo, Nicholas; Fisher, Joshua B.; Bowman, Kevin; Reager, John T.; Fahy, Kristen; Schimel, David; Fu, Rong; et al.
Abstract: A constellation of satellites is now in orbit providing information about terrestrial carbon and water storage and fluxes. These combined observations show that the tropical biosphere has changed significantly in the last 2 decades from the combined effects of climate variability and land use. Large areas of forest have been cleared in both wet and dry forests, increasing the source of carbon to the atmosphere. Concomitantly, tropical fire emissions have declined, at least until 2016, from changes in land‐use practices and rainfall, increasing the net carbon sink. Measurements of carbon stocks and fluxes from disturbance and recovery and of vegetation photosynthesis show significant regional variability of net biosphere exchange and gross primary productivity across the tropics and are tied to seasonal and interannual changes in water fluxes and storage. Comparison of satellite based estimates of evapotranspiration, photosynthesis, and the deuterium content of water vapor with patterns of total water storage and rainfall demonstrate the presence of vegetation‐atmosphere interactions and feedback mechanisms across tropical forests. However, these observations of stocks, fluxes and inferred interactions between them do not point unambiguously to either positive or negative feedbacks in carbon and water exchanges. These ambiguities highlight the need for assimilation of these new measurements with Earth System models for a consistent assessment of process interactions, along with focused field campaigns that integrate ground, aircraft and satellite measurements, to quantify the controlling carbon and water processes and their feedback mechanisms. Plain Language Summary: Changes to the carbon sequestered in tropical forests and soils, as a result of human activities and changes in rainfall, temperature, and CO2 concentrations, have a substantial impact on Earth's climate. This review summarizes recent results highlighting how the constellation of satellites now in orbit are providing new understanding of the tropical carbon cycle and how it interacts with climate variability through the water cycle, and how satellite data can be used to improve our process description of the Earth System. Key Points: Almost two decades are available of satellite measurements of multiple carbon and water tracers for quantifying tropical carbon and water states, fluxes, and interactions Substantial progress has been made in quantifying the role of water variability on carbon variability in the wet and dry tropics Satellite data provide evidence of the role of vegetation on the water cycle New measurements are needed of key states and fluxes controlling C/W interactions (e.g. soil moisture, evapotranspiration, soil carbon and respiration) to reduce uncertainty in the tropical carbon sink and its evolution Models that can integrate this wealth of data are needed to infer the hidden processes controlling carbon and water